The kindest lie ebook A novel. - Johnson, Nancy (2021)
Recommended by O Magazine * GMA * Elle * Marie Claire * Good Housekeeping * NBC News * Shondaland * Chicago Tribune * Woman's Day * Refinery 29 * Bustle * The Millions * New York Post * Parade * Hello! Magazine * PopSugar * and more! "The Kindest Lie is a deep dive into how we define family, what it means to be a mother, and what it means to grow up Black...beautifully crafted." —JODI PICOULT "A fantastic story...well-written, timely, and oh-so-memorable."—Good Morning America "The Kindest Lie is a layered, complex exploration of race and class." —The Washington Post Every family has its secrets... It's 2008, and the inauguration of President Barack Obama ushers in a new kind of hope. In Chicago, Ruth Tuttle, an Ivy-League educated Black engineer, is married to a kind and successful man. He's eager to start a family, but Ruth is uncertain. She has never gotten over the baby she gave birth to—and was forced to leave behind—when she was a teenager. She had promised her family she'd never look back, but Ruth knows that to move forward, she must make peace with the past. Returning home, Ruth discovers the Indiana factory town of her youth is plagued by unemployment, racism, and despair. As she begins digging into the past, she unexpectedly befriends Midnight, a young white boy who is also adrift and looking for connection. Just as Ruth is about to uncover a burning secret her family desperately wants to keep hidden, a heart-stopping incident strains the town's already searing racial tensions, sending Ruth and Midnight on a collision course that could upend both their lives. Powerful and unforgettable, The Kindest Lie is the story of an American family and reveals the secrets we keep and the promises we make to protect one another.